2022
DOI: 10.1007/s11218-022-09686-7
|View full text |Cite
|
Sign up to set email alerts
|

Teacher stress and burnout in Australia: examining the role of intrapersonal and environmental factors

Abstract: Concerns regarding high rates of teacher stress and burnout are present globally. Yet there is limited current data regarding the severity of stress, or the role of intrapersonal and environmental factors in relation to teacher stress and burnout within the Australian context. The present study, conducted over an 18-month period, prior to the COVID pandemic, surveyed 749 Australian teachers to explore their experience of work-related stress and burnout; differences in stress and burnout across different demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 60 publications
(87 reference statements)
3
81
0
3
Order By: Relevance
“…However, given the strong association between proactive personality and self-efficacy (Naz et al, 2020), we should consider the relevance of findings related to potential positive influence of offering stability in the educational field, developing a sense of security in attaining educational goals, and reducing external pressures (Barni et al, 2019) in the development of self-efficacy. Other research on teachers, at all levels, has demonstrated that relevant constructs to job satisfaction and proactive personality were instrumental in reducing stress and burnout, particularly the practice of emotional regulation (Carroll et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…However, given the strong association between proactive personality and self-efficacy (Naz et al, 2020), we should consider the relevance of findings related to potential positive influence of offering stability in the educational field, developing a sense of security in attaining educational goals, and reducing external pressures (Barni et al, 2019) in the development of self-efficacy. Other research on teachers, at all levels, has demonstrated that relevant constructs to job satisfaction and proactive personality were instrumental in reducing stress and burnout, particularly the practice of emotional regulation (Carroll et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Some researchers add a social aspect to the study of burnout syndrome (Arvidsson et al, 2019). Thus, the importance of the factors of emotional regulation, workload, and subjective well-being in the development of teachers' stress and the formation of certain forms of professional burnout was proven (Carroll et al, 2022). In a study of teachers' burnout symptoms, it was found that high personal selfefficacy, physical exercise, enough time for personal rest as well as high support from administration and perception of good leadership were factors leading to low-level burnout.…”
Section: Aimmentioning
confidence: 99%
“…The sudden and unstable changes in the teaching-related formats put a strain on educational settings as well as on teachers' functioning [4] and on their job demands [5]. In this vein, several studies [6][7][8][9][10] investigated the impact of those changes on teachers, showing that they had a high risk to develop stress-related symptomatology, specifically in terms of depressive symptoms and anxiety. The challenges imposed by the management of teaching activities during the COVID-19 pandemic, and the associated stress, had an impact on job burnout.…”
Section: Introductionmentioning
confidence: 99%